Electronic and photoelectron spectroscopy of substituted benzene molecules - Tuttle, William Duncan (2018)
Intramolecular vibrational redistribution (IVR) has long been investigated in para-fluorotoluene (pFT), with many comparisons made to para-difluorobenzene (pDFB). These comparisons have shown an increased IVR rate for pFT compared to pDFB at similar internal energies, and there are two factors which could influence this – the addition of the methyl group and the lowering of the symmetry of the molecule. This thesis looks to separate these two effects by introducing a comparison of pFT to para-chlorofluorobenzene, as well as an additional comparison of para-xylene (pXyl) to pDFB.